REVEALING CHARLIE GORDON’S TRAUMA IN DANIEL KEYES’S FLOWERS FOR ALGERNON - DESY EKA FATMAWATI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
Abstract Trauma is a common psychological problem of human being. Meanwhile, intelligence is a human gift as a ‘tool’ to give ‘intellectual responses’ in life. Bloom mentioned that our very complex brains and powerful memories distinguish us as the most intelligent, and yet as we will see, it is this very intelligence that leaves us vulnerable to the effects of trauma (Bloom, 1999, pp.2-3). This thesis focuses on Charlie Gordon in Daniel Keyes’s Flowers for Algernon. The purpose of this thesis is to reveal Charlie Gordon’s trauma in Flowers for Algernon. This thesis includes the analysis about Charlie’s trauma depicted in the novel, and the reasons why the trauma happens on Charlie in the novel. The writer applies library reseach method using theory of trauma and its symptoms by Judith Herman, concept of mental retardation by WHO, and concept of gifted by Sword and Silverman. In the data analysis, there are two steps which are applied: First, analyzing how the trauma depicted by using theory of trauma symptoms and theory of intelligence. The theory of trauma symptoms is applied in Charlie’s two conditions: mentally retarded man and intelligent man. Then, for knowing the role of Charlie’s intelligence in affecting his trauma, theory of intelligence which include mental retardation and genius/gifted are applied. And second, analyzing the reasons why the trauma happens on Charlie using theory of trauma. The result of this thesis shows that Charlie Gordon as retarded man, although has the trauma, does not get much effects on him. Meanwhile, the intelligent Charlie feels the effects of the trauma worse. Although individual with retarded condition is more sensitive to stress which can lead to trauma, the effect it has is less serious than individual with enough intelligence. Furthermore, the role of Charlie’s intelligence in influencing his trauma to either worsen the trauma or make it better and the reasons why the trauma happens to him are revealed. Keywords: trauma, traumatic experience, symptoms of trauma, intelligence, mental retardation, genius/gifted. Abstrak Trauma merupakan masalah psikologi yang sudah tidak asing. Sementara itu, inteligensi merupakan berkah yang dimiliki setiap individu sebagai alat untuk memberikan respon intelektual dalam hidup. Bloom menyatakan bahwa otak kita yang sangat komplek dan ingatan yang kuat membuat kita menjadi yang terpintar, akan tetapi dapat juga kita lihat, inteligensi inilah yang membuat kita lemah terhadap efek trauma (Bloom, 1999, pp.2-3). Skripsi ini terfokus pada Charlie Gordon dalam novel Daniel Keyes Flowers for Algernon. Tujuan skripsi ini ialah mengungkap trauma Charlie Gordon dalam novel Flowers for Algernon. Skripsi ini menyertakan analisa tentang trauma Charlie yang digambarkan dalam novel, dan penyebab-penyebab mengapa trauma terjadi pada Charlie dalam novel. Studi in mengaplikasikan Library Research Method, menggunakan teori trauma dan gejala trauma oleh Judith Herman, konsep mental retardasi oleh WHO, dan konsep gifted oleh Sword dan Silverman. Pada analisis data, terdapat dua langkah yang diaplikasikan: Pertama ialah menganalisis bagaimana trauma tersebut digambarkan menggunakan teori gejala trauma dan teori inteligensi. Pengaplikasian teori gejala trauma ini diaplikasikan pada dua kondisi Charlie: sebagai orang yang berkebelakangan mental dan sebagai orang yang pintar. Kemudian, untuk mengetahui peran inteligensi Charlie dalam mempengaruhi traumanya, teori inteligensi yang mencakup mental retardasi dan genius/gifted juga diaplikasikan. Langkah kedua ialah menganalisis penyebab mengapa trauma tersebut terjadi pada Charlie menggunakan teori trauma. Hasil skripsi ini menunjukan bahwa ketika Charlie menjadi seorang berketerbelakangan mental, walaupun ia mempunyai trauma, ia tidak merasakan efek yang berat pada dirinya. Sementara itu, Charlie sebagai seorang yang pintar merasakan efek trauma lebih parah. Walaupun individu dengan keterbelakangan mental lebih sensitif terhadap stress yang dapat mengarah pada trauma, efek yang didapat tidak seserius individu dengan inteligensi yang cukup. Lebih jauh, peran inteligensi Charlie dalam mempengaruhi traumanya menjadi parah atau menjadi lebih baik dan penyebab mengapa trauma tersebut terjadi padanya juga terungkap. Keywords: trauma, pengalaman traumatik, gejala-gejala trauma, inteligensi, mental retardasi, genius/gifted.